SERIES: ECONOMICS APPLIED TO PROCESS ENGINEERING (Part 7) PROUCTO DECISIONS OR DELETE A FACTORY - Porlles Loarte, José Angel (2007)
In the present world-wide context. the hard competition generates that the diversified companies, in certain circumstances must contemplate the possibility of closing or of eliminating a line of product or one of its factories. The intention of this seventh part provides the excellent methodology and criteria in the economic analysis to evaluate this situation, that allows to adopt the suitable course of action more.